Entity matching with similarity encoding: A supervised learning recommendation framework for linking (big) data - Pantelis Karapanagiotis; Marius Liebald (Leibniz Institute for Financial Research SAFE, 2023)
In this study, we introduce a novel entity matching (EM) framework. It com-bines state-of-the-art EM approaches based on Artificial Neural Networks (ANN) with a new similarity encoding derived from matching techniques that are preva-lent in finance and economics. Our framework is on-par or outperforms alternative end-to-end frameworks in standard benchmark cases. Because similarity encod-ing is constructed using (edit) distances instead of semantic similarities, it avoids out-of-vocabulary problems when matching dirty data. We highlight this property by applying an EM application to dirty financial firm-level data extracted from historical archives.
Keywords: C8; 330; Entity matching; Entity resolution; Database linking; Machine learning; Record resolution; Similarity encoding